Obstructive Sleep Apnea, Platelet Aggregation, and Cardiovascular Risk - Zanetta Kovbasyuk; Jaime Ramos‐Cejudo; Ankit Parekh; Omonigho M. Bubu; Indu A. Ayappa; Andrew W. Varga; Ming‐Huei Chen; Andrew D. Johnson; Eugenio Gutierrez‐Jimenez; David M. Rapoport; Ricardo S. Osorio (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Although related, the precise mechanisms linking obstructive sleep apnea (OSA) and cardiovascular disease (CVD) are unclear. Platelets are mediators of CVD risk and thrombosis and prior studies suggested associations of OSA and platelet activity. The aim of this study is to assess the link between OSA, platelet activity, and CVD‐related risk factors. Methods and Results We studied the association of OSA‐measures and platelet aggregation in participants dually enrolled in the SHHS (Sleep Heart and Health Study) and FHS (Framingham Heart Study). We applied linear regression models with adjustment for demographic and clinical covariates and explored interactions with OSA and CVD‐related factors, including age, sex, body mass index, hypertension, OSA diagnosis (apnea‐hypopnea index 4%≥5), and aspirin use. Our final sample was of 482 participants (60 years [14.00], 50.4% female). No associations were observed between apnea‐hypopnea index 4% and platelet aggregation in the main sample. Stratified analysis revealed an association in aspirin users (n=65) for our primary exposure (apnea‐hypopnea index 4%, β=0.523; P<0.001; n=65), and secondary exposures: hypoxic burden (β=0.358; P<0.001), minimum saturation (β=−0.519; P=0.026), and oxygen desaturation index 3% (β=74.672; P=0.002). No associations were detected in nonaspirin users (n=417). Conclusions No associations were detected between OSA and platelet aggregation in a community sample. Our finding that OSA associates with increased platelet aggregation in the aspirin group, most of whom use it for primary prevention of CVD, suggests that platelet aggregation may mediate the adverse impact of OSA on vascular health in individuals with existing CVD risk, supporting further investigation.